Novel Stemness-Related Gene Signature Predicting Prognosis and Indicating a Different Immune Microenvironment in HNSCC - Luo, Yi; Xu, Wei-Bo; Ma, Ben; Wang, Yu (Frontiers in Genetics, 2022)
Background: The head and neck squamous cell carcinomas (HNSCC) is one of the most frequent cancers in the world, with an unfavorable prognosis. Cancer stem cells (CSCs) have been found to be responsible for HNSCC recurrence and therapeutic resistance. Methods: The stemness of HNSCC was measured using a stemness index based on mRNA expression (mRNAsi). Stemness-related genes were discovered using weighted gene co-expression network analysis, least absolute shrinkage and selection operator analysis, and Cox regression, and a stemness-related prognostic index (SPI) was constructed. This research was based on TCGA and GSE65858. Results: Stemness was found upregulated in HNSCC compared with normal tissues. The risk score model including five stemness-related genes exhibited a good accuracy in predicting outcomes. High SPI predicted a shorter overall survival (OS) in HNSCC patients, in the meantime, also demonstrated a lower CD8+ T cell infiltration and a higher enrichment of macrophages and fibroblasts than the low-SPI group, focusing on several up-regulated pathways such as epithelial mesenchymal transition (EMT), MYC targets v1, E2F targets, mTORC1 signaling, hypoxia, MYC targets v2, angiogenesis, G2M checkpoint, and glycolysis. Conclusion: The SPI signature, which includes five stemness-related genes, could be utilized as a prognostic biomarker for HNSCC, implying that stemness may impact HNSCC immunologic profiles and be a feasible therapeutic target.